Non‐medical use of prescription opioids and prescription opioid‐related harms: why so markedly higher in North America compared to the rest of the world?. (20th May 2013) - Fischer, Benedikt; Keates, Annette; Bühringer, Gerhard; Reimer, Jens; Rehm, Jürgen
Abstract Aims This paper aims to identify possible system‐level factors contributing to the marked differences in the levels of non‐medical prescription opioid use (NMPOU) and prescription opioid (PO)‐related harms in North America (i.e. the United States and Canada) compared to other global regions. Methods Scientific literature and information related to relevant areas of health systems, policy and practice were reviewed and integrated. Results We identified several but different factors contributing to the observed differences. First, North American health‐care systems consume substantially more Pos—even when compared to other high‐income countries—than any other global region, with dispensing levels associated strongly with levels of NMPOU and PO‐related harms. Secondly, North American health‐care systems, compared to other systems, appear to have lesser regulatory access restrictions for, and rely more upon, community‐based dispensing mechanisms of POs, facilitating higher dissemination level and availability (e.g. through diversion) of POs implicated in NMPOU and harms. Thirdly, we note that the generally high levels of psychotrophic drug use, dynamics of medical–professional culture (including patient expectations for 'effective treatment'), as well as the more pronounced 'for‐profit' orientation of key elements of health care (including pharmaceutical advertising), may have boosted the PO‐related problems observed in North America. Conclusions Differences in the organization of health systems, prescription practices, dispensing and medical cultures and patient expectations appear to contribute to the observed inter‐regional differences in non‐medical prescription opioid use and prescription opioid‐related harms, although consistent evidence and causal analyses are limited. Further comparative examination of these and other potential drivers is needed, and also for evidence‐based intervention and policy development.